Enhancing The Speaking Skill Using Metacognitive Strategy - Ismit Karim (Jurnal Langua, 2019)
This paper reports a qualitative case study which aims to investigate the use of metacognitive strategy in developing the autonomous students’ speaking skill which is based on the participants' metacognitive awareness and kind of metacognitive strategy use. There were 6 autonomous learners who are considered as high-achiever students which took part as the participants through purposive sampling. The in-depth interview based on the Strategy Inventory for Language Learning (SILL) was chosen in order to grasps the data regarding their speaking learning using metacognitive strategies which then analyzed using thematic analysis. The findings revealed that most of the High-Achiever students were having difficulties in their speaking learning as they were just started to study proper English when they decided to attend the university. Thus, to allow them in make the best use of their metacognitive strategy, they applied cognitive knowledge strategies and socio-affective strategies in dealing with their metacognitive processes such planning, monitoring and evaluation in their speaking learning. Moreover, in developing their metacognitive awareness, the participants were found affected to two factors; Self-appraisal and self-management.